Antibacterial performance on plasma polymerized heptylamine films loaded with silver nanoparticles. (16th December 2016) - Lin, Yu-Chun; Lin, Chia-Chun; Lin, Chih-Hao; Wang, Meng-Jiy
Abstract: The antibacterial performance of the plasma-polymerized (pp) heptylamine thin films loaded with silver nanoparticles was evaluated against the colonization of Escherichia coli and Staphylococcus aureus . The properties including the thickness and chemical composition of the as deposited HApp films were modulated by adjusting plasma parameters. The acquired results showed that the film thickness was controlled in the range of 20 to 400 nm by adjusting deposition time. The subsequent immersion of the HApp thin films in silver nitrate solutions result in the formation of amine-metal complexes, in which the silver nanoparticles were reduced directly on the matrices to form Ag@HApp. The reduction reaction of silver was facilitated by applying NaBH4 as a reducing agent. The results of physicochemical analyses including morphological analysis and ellipsometry revealed that the silver nanoparticles were successfully reduced on the HApp films, and the amount of reduced silver was closely associated which the thickness of the plasma-polymerized films, the concentration of applied metal ions solutions, and the time of immobilization. Regarding the antibacterial performance, the Ag@HApp films reduced by NaBH4 showed antibacterial abilities of 70.1 and 68.2% against E. coli and S. aureus, respectively.